Assessment of abusive supervision – BOSS methodology - Birknerová, Zuzana; Zbihlejová, Lucia; Droppa, Milan (Journal of Business Economics and Management, 2021)
Concerning the issue of conceptualization and operationalization of abusive supervision, contemporary studies including the one presented below discuss several issues. The presented paper is aimed at the downward (vertical) form of workplace bullying, described in literature as abusive supervision or bossing, and the form of its assessment within the work environment. Furthermore, a new original methodology designed to measure bossing psychometrically, is proposed and labeled as BOSS. On the basis of the research results, which involved participation of 525 respondents (non-managerial workers; 40% men and 60% women), two factors of the BOSS methodology were extracted and labeled as: Communication-Aimed Bossing and Psyche-Aimed Bossing. Bossing is typically manifested within two distinct areas represented by these extracted factors. The full version of the BOSS methodology is also presented in the paper. First published online 27 November 2020